Zhodnocení finanční situace podniku a návrhy na její zlepšení - Málková, Markéta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zabývá zhodnocením finanční situace daného podniku dle vybraných metod finanční analýzy. Teoretická část vymezuje základní pojmy, metody a ukazatele finanční analýzy, které slouží pro zpracování praktické části. Na základě zhodnocení finanční situace podniku získaných z výsledků finanční analýzy jsou prezentovány možnosti návrhů a doporučení, které by měly vést ke zlepšení hospodaření podniku. Na základě zjištěných skutečností bylo shledáno, že společnost v současné době nemá správě nastavený systém pro řízení odběratelských vztahů, tvorbu, použití a účtování o opravných položkách k pohledávkám. Pro dosažení zlepšení byla určena doporučení

The diploma thesis deals with the assessment of the financial situation of the company concerned according to the selected methods of financial analysis. The theoretical part of the thesis defines the basic concepts, methods, and the indicators of financial analysis, which is used for processing of the practical part. On the basis of the assessment of the financial situation of the company derived from the results of the financial analysis there are presented options, proposals and recommendations. They should lead to the improvement of the management of the mentioned company. There was found that the company has currently no settings management system for customer relationship management, creation, using and accounting of adjustments to receivables. To achieve improvements there were recommendations.
Financial Statements Analysis in a Company and Proposals for Improvements of Financial Health
Keywords: Finanční řízení podniku; účetní výkazy; strategická analýza; finanční analýza; hodnocení finanční situace; Financial Management; Financial statements; Strategic Analysis; Financial Analysis; Financial health